PRAWO WYZNANIOWE W PRAKTYCE III RP (zagadnienia wybrane) - Szymanek, Jarosław (Wydział Prawa i Administracji UAM, 2006)
The paper focuses on the analysis of the legal regulations governing the relations between the state and the church in Poland. Today, the constitutional regulations regarding the widely understood denominational issues are regarded to be a constitutional matter. This means that each constitution must contain at least those fundamental laws that regulate the individual sphere (freedom of conscience and freedom of religion) and the institutional (collective) sphere, the subject of which are the provisions regulating the state-church relations. It is recognised that only when those two are combined the constitutional matter regarding the religious denominational sphere is exhausted. The denominational matter, apart from the fact of being an obligatory element of each modern, comprehensive constitution, is also that fragment of its provisions which is always a controversial issue, both during the legislative process, and subsequently, when the law is to be implemented or executed. The most controversial issues in Poland (either when it comes to their legal articulation or practical application) include the general rule of equal rights granted to every denomination; the principle of independence and autonomy of the state and church; and the consensular form of relations between the state and churches other than the Roman Catholic Church. The controversies which occur are the best indication how sensitive the issue of religious denominations still is in Poland. The example of the law on religious denominations in Poland shows best, at least at the constitutional law level, that the so called constitution in book is often very far from the constitution in action.
LAW ON RELIGIOUS DENOMINATIONS IN POLAND AFTER 1991